Информационная безопасность: концепция и средства обеспечения - Серков, Александр Анатольевич; Певнев, В. Я. (НТУ "ХПИ", 2008)
Розглянуто існуючі визначення інформаційної безпеки, виявлені недоліки цих визначень. Запропоновано визначення інформаційної безпеки, які базуються на системному підході. Розглянуто функції інформаційної безпеки з точки зору властивості інформації та засобів її забезпечення.

The existing determinations of information security are considered; the defects of these determinations are determined. The determination of information security, which based on system approaches are proposed. They functions of information security with standpoint of characteristics of information and facilities of there provisions are considered.
Keywords: ИБ; морально-этические нормы; МЭН; технические средства защиты информации; ТСЗИ; телекоммуникационная сеть; защита информации